2017
DOI: 10.1167/iovs.16-20692
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 Activation Initiates Photoreceptor Cell Death In Vivo and In Vitro

Abstract: PURPOSE. Accumulating evidence has demonstrated that excessive immunoreaction plays a prominent role in the pathogenesis of dry AMD. Toll-like receptor 3 (TLR3) can be activated by double-stranded (ds)RNA in retinal pigment epithelia and trigger an innate immunitymediated inflammatory response. However, its role in photoreceptor cells, the effectors of AMD geographic atrophy, remains unclear.METHODS. The expression of TLR3 was examined in mouse retina and in a murine photoreceptor cell line (661W). Retinal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Of particular interest were those genes that were upregulated in light-triggered Cln3 Δex7/8 animals compared to light-damaged wild-type mice and in turn downregulated with minocycline treatment. Irf7 and Zbp1 , two genes that regulate immune responses and are associated with neuronal cell loss, are highly upregulated in CLN3-deficient and light-triggered mice, and are examples for a possible overshooting immune reaction already described for CLN3-deficient primary microglia ( DeFilippis et al, 2010 ; Gao et al, 2017 ; Mustafi et al, 2012 ; Xiong and Kielian, 2013 ).…”
Section: Discussionmentioning
confidence: 92%
“…Of particular interest were those genes that were upregulated in light-triggered Cln3 Δex7/8 animals compared to light-damaged wild-type mice and in turn downregulated with minocycline treatment. Irf7 and Zbp1 , two genes that regulate immune responses and are associated with neuronal cell loss, are highly upregulated in CLN3-deficient and light-triggered mice, and are examples for a possible overshooting immune reaction already described for CLN3-deficient primary microglia ( DeFilippis et al, 2010 ; Gao et al, 2017 ; Mustafi et al, 2012 ; Xiong and Kielian, 2013 ).…”
Section: Discussionmentioning
confidence: 92%
“…Controversially, the activation of TLR might also create a degenerative effect in neuron cells; for example, Chintala et al's work showed that poly(I:C)-induced TLR3 activation upregulated the protein level of MAPK JNK3 and promoted the degeneration of RGCs in mouse eye [ 61 ]. Similarly, Gao et al's work showed that poly(I:C)-induced TLR3 evoked an inflammatory response and cell death both in murine photoreceptor 661W cells and an in vivo model [ 62 ]. Therefore, the role of TLR in prosurvival or pro-cell death of neuron cells may depend on the types [ 55 ] of stimuli, the level [ 60 ] of stimuli, and the downstream of TLR signaling [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 661W cells were cultured in Dulbecco's modified Eagle's medium (Life Technologies) containing 10% fetal bovine serum (Gibco, Waltham, MA; Thermo Fisher Scientific) and 100 U/mL penicillin-streptomycin (Thermo Fisher Scientific). 30 …”
Section: Methodsmentioning
confidence: 99%